A special fructose bisphosphate functions as a cytoplasmic regulatory metabolite in green leaves - Cséke, Csaba (1982)
Fructose 2,6-bisphosphate (Fru-2,6-P(2)), a regulatory metabolite discovered in animal cells and recently reported to occur in etiolated seedlings, was found to be present in the cytoplasmic fraction of leaves of spinach and peas (typical C(3) plants, in which a three-carbon carboxylic acid is a major early photosynthetic product). At concentrations approximating those calculated to occur physiologically, Fru-2,6-P(2) modulated two enzymes of the leaf cytoplasm: (i) Fructose-1,6-bisphosphatase (EC 3.1.3.11), a key enzyme of sugar synthesis, was competitively inhibited by Fru-2,6-P(2), and (ii) pyrophosphate-linked phosphofructokinase (inorganic pyrophosphate-D-fructose-6-phosphate 1-phosphotransferase, EC 2.7.1.90), a cytoplasmic enzyme that now seems important in glycolysis of C(3) plants, was activated by Fru-2,6-P(2). There was no indication of a role for Fru-2,6-P(2) in photosynthesis of either chloroplasts or oxygenic prokaryotes. The results suggest that Fru-2,6-P(2) functions in the regulation of glycolysis and gluconeogenesis (carbohydrate synthesis) in the cytoplasm of leaves of C(3) plants.